Patient satisfaction with ultrasound, whole-body CT and whole-body diffusion-weighted MRI for pre-operative ovarian cancer staging: a multicenter prospective cross-sectional survey - Pinto, Patrícia; Valentin, Lil; Borčinová, Martina; Wiesnerová, Markéta; Filip, Fruhauf; Burgetova, Andrea; Masek, Martin; Lambert, Lukas; Chiappa, Valentina; Franchi, Dorella; Testa, Antonia Carla; Moro, Francesca; et al. (International journal of gynecological cancer, 2024)
BACKGROUND: In addition to the diagnostic accuracy of imaging methods, patient-reported satisfaction with imaging methods is important. OBJECTIVE: To report a secondary outcome of the prospective international multicenter Imaging Study in Advanced ovArian Cancer (ISAAC Study), detailing patients' experience with abdomino-pelvic ultrasound, whole-body contrast-enhanced computed tomography (CT), and whole-body diffusion-weighted magnetic resonance imaging (WB-DWI/MRI) for pre-operative ovarian cancer work-up. METHODS: In total, 144 patients with suspected ovarian cancer at four institutions in two countries (Italy, Czech Republic) underwent ultrasound, CT, and WB-DWI/MRI for pre-operative work-up between January 2020 and November 2022. After having undergone all three examinations, the patients filled in a questionnaire evaluating their overall experience and experience in five domains: preparation before the examination, duration of examination, noise during the procedure, radiation load of CT, and surrounding space. Pain perception, examination-related patient-perceived unexpected, unpleasant, or dangerous events ('adverse events'), and preferred method were also noted. RESULTS: Ultrasound was the preferred method by 49% (70/144) of responders, followed by CT (38%, 55/144), and WB-DWI/MRI (13%, 19/144) (p<0.001). The poorest experience in all domains was reported for WB-DWI/MRI, which was also associated with the largest number of patients who reported adverse events (eg, dyspnea). Patients reported higher levels of pain during the ultrasound examination than during CT and WB-DWI/MRI (p<0.001): 78% (112/144) reported no pain or mild pain, 19% (27/144) moderate pain, and 3% (5/144) reported severe pain (pain score >7 of 10) during the ultrasound examination. We did not identify any factors related to patients' preferred method. CONCLUSION: Ultrasound was the imaging method preferred by most patients despite being associated with more pain during the examination in comparison with CT and WB-DWI/MRI. TRIAL REGISTRATION NUMBER: NCT03808792.
Keywords: senioři; Cross-Sectional Studies; senioři nad 80 let; Tomography, X-Ray Computed; Patient Satisfaction; Middle Aged; průřezové studie; nádory vaječníků; Prospective Studies; Adult; Diffusion Magnetic Resonance Imaging; difuzní magnetická rezonance; Aged, 80 and over; Neoplasm Staging; ultrasonografie; ženské pohlaví; Ovarian Cancer; Humans; prospektivní studie; Whole Body Imaging; lidé středního věku; spokojenost pacientů; Ultrasonography; staging nádorů; dospělí; počítačová rentgenová tomografie; Female; Ovarian Neoplasms; celotělové zobrazování; Aged; Preoperative Care; předoperační péče; lidé